181k views
3 votes
Someone help me out please

Someone help me out please-example-1
User Ootterskog
by
6.2k points

1 Answer

2 votes

1 step (B): raise both sides of the equation to the power of 2.


(√(x+3)-√(2x-1))^2=(-2)^2,\\ (x+3)-2√(x+3)\cdot √(2x-1)+(2x-1)=4,\\ 3x+2-2√(x+3)\cdot √(2x-1)=4.

2 step (A): simplify to obtain the final radical term on one side of the equation.


-2√(x+3)\cdot √(2x-1)=4-3x-2,\\ -2√(x+3)\cdot √(2x-1)=2-3x,\\ 2√(x+3)\cdot √(2x-1)=3x-2.

3 step (F): raise both sides of the equation to the power of 2 again.


(2√(x+3)\cdot √(2x-1))^2=(3x-2)^2,\\ 4(x+3)(2x-1)=(3x-2)^2.

4 step (E): simplify to get a quadratic equation.


4(2x^2-x+6x-3)=(3x)^2-2\cdot 3x\cdot 2+2^2,\\ 8x^2+20x-12=9x^2-12x+4,\\ x^2-32x+16=0.

5 step (D): use the quadratic formula to find the values of x.


D=(-32)^2-4\cdot 16=1024-64=960, \\ √(D) =8√(5) ,\\ x_(1,2)=(32\pm 8√(5))/(2) =16\pm 4√(5).

6 step (C): apply the zero product rule.


x^2-32x+16=(x-16-4√(5)) (x-16+4√(5)) ,\\ (x-16-4√(5)) (x-16+4√(5)) =0,\\ x_1=16+4√(5) ,x_2=16-4√(5).

Additional 7 step: check these solutions, substituting into the initial equation.

User Nadimibox
by
6.3k points